Efficacy of a Soft Release Strategy for Translocating Scaled Quail in the Rolling Plains of Texas - Rebekah E. Ruzicka; Kara B. Campbell; Michelle C. Downey; Dale Rollins; Bradley Kubečka; Matthew Poole; Donald C. Ruthven (National Quail Symposium Proceedings, 2017)
Scaled Quail (Callipepla squamata) populations have become locally extinct and spatially fragmented in the Rolling Plains ecoregion of Texas. Translocating Scaled Quail from core to declining populations could augment populations or re-establishing extinct populations. Although translocations of scaled quail have been attempted in Texas, none have been documented and none have attempted to identify best practices. Release strategy (i.e., hard or soft release) is a factor that can influence the success of a translocation. Our objective was to compare daily apparent survival of scaled quail translocated to the Rolling Plains between 2 release treatment groups: hard- and soft-release. We estimated a daily apparent survival rate (DASR) for radio-marked hens during the breeding season as a function of age, release treatment, and a time trend. We found evidence of a positive effect of the soft release treatment and higher DASR in adult hens. Overall, DASR of translocated hens was low compared to reported estimates of survival in established resident populations. Using a soft release strategy and translocating a greater proportion of adults may improve future translocation success for scaled quail.
Keywords: callipepla squamata; dispersal; reintroduction; scaled quail; survival; translocation